1314 Effect of Blood Transfusion on Lipid Peroxidation Products in Sick Neonates - an Exploratory Study. (October 2012) - Mukhopadhyay, K; Ali, M; Bhattacharya, S; Kumar, P
Abstract : Background and Aims: Preterm neonates have lower anti oxidant defense system and repeated blood transfusion may further increase the oxidative stress specially in sick preterm neonates. The aim was to assess the effect of blood transfusion on lipid peroxidation product Malondialdehyde (MDA) in sick neonates. Methods: This was an exploratory study in a Level III neonatal unit in which 50 consecutive sick neonates of ≤34weeks gestation were enrolled who received blood transfusion till day 28. Primary outcomes were Pre and post transfusion blood and Urine MDA and Pre transfusion SOD and Catalase. Secondary outcome was Pretransfusion MDA and antioxidant enzymes in various neonatal morbidities. Results: The mean birth weight and gestational age were 1416±219 grams and 29.9±2.5 weeks respectively. The pre transfusion blood and urine MDA were 4.2±1.2 nmol/ml and 6.96±3.7 nmol/ml respectively. These levels increased significantly from baseline after each transfusion. Base line MDA was higher (p=0.032) and SOD (p=0.02) and Catalase (p=0.00) were significantly lower in babies < 30 wks gestation. Pre transfusion Blood MDA levels were significantly higher (p=0.00) in the babies who had IVH and BPD while urine MDA was significantly high in BPD babies. SOD and Catalase levels were significantly (p=0.00) lower in babies who developed BPD. Conclusion: Baseline oxidant levels are higher and anti- oxidant enzymes are lower in in < 30 weeks gestation babies and in those who developed BPD and IVH. Blood transfusion further increases lipid peroxidation products.